WHALE SHARK RHINCODON TYPUS SMITH CAUGHT OFF CALICUT - Seshappa, G; Chennubhotla, V S K; Nair, K V Somasekharan (Indian Journal of Fisheries, 2011)
A juvenile male specimen of Rhincodon typus Smith measuring 5600 mm was caught off Calicut during the month of January 1970. The body measurements and a brief description of the specimen are given